IDENTIFICATION AND ANTIBACTERIAL ACTIVITY TEST OF ENDOPHYTE FUNGI MAHONI BARK (Swieenia mahagoni L.) IFKBM04 - Nuryanti, Siska; Rosdah, Rosdah; Naid, Tadjuddin; Hardiyanti, Vivi (Fakultas Farmasi, Universitas Muslim Indonesia, 2021)
Endophytes represent a complex community of microorganisms colonizing asymptomatically internal tissues of higher plants. Several reports have shown that endophytes enhance the fitness of their host plants by direct production of bioactive secondary metabolites. This study investigated the antibacterial activity of endophytes fungi IFKBM04 isolated from Swietenia mahagoni L. and identified macroscopic and microscopic characteristics of endophytic fungi. Based on the results of macroscopic and microscopic identification compared with the literature to determine the general characteristics of the sample. The results of this morphological identification showed that the sample of mahogany bark isolate (Swietenia mahagoni L.) code IFKMB-04 had similarities with the genus Saccharomyces sp.